Reflexões sobre a HQ do Pantera Negra e suas correlações entre o ensino e aprendizagem a respeito da História da África - Silva, Renato Cavalcante da (2020)
The present research deals with the possible uses of the magazine in Black Panther squares with the aim of teaching and learning themes involving the History of Africa for classes at high school levels. The Black Panther was the first African black superhero in the history of comics, this character had an odd meaning in the development of a pedagogical work that seeks to reflect issues such as identity, representativeness, appreciation of African black history and culture. The research interpreted the HQ as chronicles of the everyday concept developed by the historian Fábio Viera Guerra and, also placed this object within the field of thought of the history culture having as main interlocutor the philosopher Jörn Rüsen.